Diurnal changes in glutamate + glutamine levels of healthy young adults assessed by proton magnetic resonance spectroscopy - Volk, Carina (Hum Brain Mapp, 2018)
The glutamatergic α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor is involved in synaptic plasticity processes, and animal studies have demonstrated altered expression across the sleep wake cycle. Accordingly, glutamate levels are reduced during non‐rapid eye movement (NREM) sleep and the rate of this decrease is positively correlated with sleep EEG slow wave activity (SWA). Here, we combined proton magnetic resonance spectroscopy ((1)H‐MRS) and high‐density sleep EEG to assess if (1)H‐MRS is sensitive to diurnal changes of glutamate + glutamine (GLX) in healthy young adults and if potential overnight changes of GLX are correlated to SWA. (1)H‐MRS was measured in the parietal lobe in the evening and in the subsequent morning. High‐density sleep EEG was recorded overnight between the evening and morning scans. Our results revealed a significant overnight reduction in GLX, but no significant changes in other metabolites. The decrease in GLX positively correlated with the decrease of SWA. Our study demonstrates that quantification of diurnal changes in GLX is possible by means of (1)H‐MRS and indicates that overnight changes in GLX are related to SWA, a marker that is closely linked to the restorative function of sleep. This relationship might be of particular interest in clinical populations in which sleep is disturbed.